CODG TEC VARIATION DURING SOLAR MAXIMUM AND MINIMUM OVER NIAMEY - Christian, Zoundi; Frederic, Ouattara; Emmanuel, Nanema; Rolland, Fleury; Francois, Zougmore (European Scientific Journal, ESJ, 2013)
The present paper analyses the prediction of CODG model during solar maximum and solar minimum at Niamey station (Geo Lat 13°28’45.3”N; Geo long: 02°10’59.5”E). CODG TEC only shows dome time profile. The estimated TEC is higher during solar maximum than during solar minimum. Spring estimated TEC is the highest and summer one the lowest. The equinoctial asymmetry is only observed during solar minimum phase.